2020
DOI: 10.1158/1541-7786.mcr-19-0768
|View full text |Cite
|
Sign up to set email alerts
|

Current Perspectives on Circulating Tumor DNA, Precision Medicine, and Personalized Clinical Management of Cancer

Abstract: Circulating tumor DNA (ctDNA) has recently emerged as a minimally invasive "liquid biopsy" tool in precision medicine. ctDNA-genomic DNA fragments that are released into the bloodstream after the active secretion of microvesicles or tumor cell lysis reflects tumor evolution and the genomic alterations present in primary and/or metastatic tumors. Notably, ctDNA analysis might allow the stratification of patients, the monitoring of the therapeutic response, and the establishment of an opportunity for early inter- Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 90 publications
1
60
0
Order By: Relevance
“…Novel methods such as circulating tumour DNA sequencing could be utilised to avoid sampling bias and increase the number of patients for whom genomic information is available. Nevertheless there are still cases of discordance between circulating tumour DNA and tumour DNA from sequenced samples, and plasma sampling has a higher rate of false negatives [1,46]. Secondly, a panel of the size employed in this study cannot accurately estimate the true total mutation burden, and the mutation number per sample reported here cannot be considered a surrogate measure.…”
Section: Discussionmentioning
confidence: 90%
“…Novel methods such as circulating tumour DNA sequencing could be utilised to avoid sampling bias and increase the number of patients for whom genomic information is available. Nevertheless there are still cases of discordance between circulating tumour DNA and tumour DNA from sequenced samples, and plasma sampling has a higher rate of false negatives [1,46]. Secondly, a panel of the size employed in this study cannot accurately estimate the true total mutation burden, and the mutation number per sample reported here cannot be considered a surrogate measure.…”
Section: Discussionmentioning
confidence: 90%
“…In 2016, the cobas EGFR mutation test 2 (Roche Molecular Systems), which is capable of detecting 42 different EGFR mutations in exons 18-21 in tissue-derived as well as plasma-derived DNA, received the FDA approval. The study of the use of this test in the NSCLC patients enrolled in the ENSURE trial concluded that ctDNA assay could be recommended as a suitable alternative to tissue biopsy analysis for the assessment of EGFR mutational status [107,108]. Importantly, the Liquid Long-O-Cohort trial involving the evaluation of the efficacy of Osimertinib through ctDNA analysis of NSCLC patients using the Cobas EGFR mutation test 2 recommended ctDNA analysis as a feasible alternative to tumor biopsies for the screening of acquired EGFR T790M resistance mutation [105].…”
Section: Lung Cancermentioning
confidence: 99%
“…Certain clinical trials currently under progress, such as the MELROSE phase II trial, have included ctDNA analysis as a tool for evaluating the genetic tumor profile at the time of disease progression in the NSCLC patients undergoing treatment with Osimertinib [107], while other studies have supported the capacity of ctDNA assay to detect other genetic alterations observed in NSCLC, such as ALK or ROS1 translocations [108].…”
Section: Lung Cancermentioning
confidence: 99%
“…Jeremy et al [4] has conducted a survey concerning global incidence of prostate cancer in developing and developed countries and revealed that the global incidence of prostate cancer has been increasing in most countries, especially in Asia, Northern and Western Europe [5]. Although the therapeutic strategies for prostate cancer are varied, the genetic heterogeneity among different prostate cancer patients make the precision medicine gradually important and popular in the treatment of prostate cancer [6][7][8].…”
Section: Introductionmentioning
confidence: 99%